Factors Associated With American Indian and White Adolescent Drug Selling in Rural Communities - Eitle, David (Int J Law Crime Justice, 2014)
Relatively few studies have examined the correlates of adolescent drug selling in America, with most of these studies focusing on urban settings. The present study examines the risk and protective factors associated with drug selling among American Indian and white adolescents residing in a rural Northwestern state in the United States. Using survey data collected in 2010-2012, we conduct logistic regression analyses exploring the correlates of drug selling (n=568). Generally, we found support for prior explanations of drug selling, but identified some important race-specific differences. Specifically, we found that stress exposure was a risk factor for American Indians, but not whites. Conversely, academic achievement served as a protective factor for white adolescents but not American Indians. Our findings suggest that the race gap in rural drug selling can be explained by considering differences in social bonds, stress exposure, and exposure to substance using family and friends.